DNA methylation derived systemic inflammation indices are associated with head and neck cancer development and survival - Ambatipudi, Srikant (Oral Oncol, 2018)
OBJECTIVES: Head and neck squamous cell carcinoma (HNSCC) is often associated with chronic systemic inflammation (SI). In the present study, we assessed if DNA methylation-derived SI (mdSI) indices: Neutrophil-to- Lymphocyte ratio (mdNLR) and Lymphocyte-to-Monocyte ratio (mdLMR) are associated with the presence of HNSCC and overall survival (OS). MATERIALS AND METHODS: We used two peripheral blood DNA methylation datasets: an HNSCC case-control dataset (n = 183) and an HNSCC survival dataset (n = 407) to estimate mdSI indices. We then performed multivariate regressions to test the association between mdSI indices, HNSCC development and OS. RESULTS: Multivariate logistic regression revealed that elevated mdNLR was associated with increased odds of being an HNSCC case (OR = 3.25, 95% Cl = 2.14–5.34, P = 4× 10-(7)) while the converse was observed for mdLMR (OR = 0.88, 95% Cl = 0.81–0.90, P = 2 × 10(−3)). In the HNSCC survival dataset, HPV16-E6 seropositive HNSCC cases had an elevated mdLMR (P = 9 × 10(−5)) and a lower mdNLR (P = 0.003) compared to seronegative patients. Multivariate Cox regression in the HNSCC survival dataset revealed that lower mdLMR (HR = 1.96, 95% Cl = 1.30–2.95, P = 0.0013) but not lower mdNLR (HR = 0.68, 95% Cl = 0.46–1.00, P = 0.0501) was associated with increased risk of death. CONCLUSION: Our results indicate that mdSI estimated by DNA methylation data is associated with the presence of HNSCC and overall survival. The mdSI indices may be used as a valuable research tool to reliably estimate SI in the absence of cell-based estimates. Rigorous validation of our findings in large prospective studies is warranted in the future.